Impact of active methodologies on the digital competencies of elderly - Martínez-Alcalá, Claudia I.; Cabero-Almenara, Julio; Martínez-Lazcano, Verónica; Aguilar-Lira, Lizbeth; González-Vera, Cinthia N. (Frontiers in Education, 2024)
It is essential to develop digital skills in the demographic group represented by elderly once digital exclusion becomes a growing concern in an increasingly technological world. This study aims to evaluate the effectiveness of flipped classrooms and microlearning on the digital literacy of adults over 50 years through a virtual course. With the implementation of a descriptive, correlational, and longitudinal approach, the research considered six consecutive two-month periods, ranging from elemental to advanced levels of expanding their digital skills. The final sample included 112 Mexican participants (93 women and 19 men) with a mean age of 64.30 years and an average schooling of 13.6 years. The results reveal that participants’ satisfaction with the pedagogical approaches is positively associated with developing their digital skills and increasing their confidence to apply them. Altogether, these findings highlight how a structured learning environment, combined with emotional support and active practice, not only facilitates the acquisition of technology skills but also empowers older people, enabling them to approach the digital world with confidence. In conclusion, this study emphasizes the importance of implementing pedagogical approaches that address the specific needs of elderly, promoting their digital inclusion and the development of their autonomy in the use of technology.